2014
DOI: 10.1007/s11010-014-2068-5
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor-BB induces matrix metalloproteinase-2 expression and rat vascular smooth muscle cell migration via ROCK and ERK/p38 MAPK pathways

Abstract: Matrix metalloproteinases (MMP) play a pivotal role in the pathogenesis of cardiovascular diseases. Their expressions are altered in response to a variety of stimuli, including growth factors, inflammatory markers, and cytokines. In this study, we demonstrated that platelet-derived growth factor-BB (PDGF-BB) induces a dose- and time-dependent increase in MMP-2 expression in rat vascular smooth muscle cells (VSMC). Treatment with either the Rho-associated protein kinase (ROCK) inhibitor Y-27632 or suppression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…PDGF, mainly expressed in VSMCs and endothelial cells, promote mitosis and play an important role in the proliferation of VSMCs [6][7][8]37]. The binding of PDGF-BB, a subtype of PDGF released from injured vessels, to its receptor can trigger the activation of downstream and then contribute significantly to VSMCs proliferation [9][10][11][12]. In this paper, PDGF-BB could effectively induce MOVAS proliferation, which was consistent with the previous studies reported.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…PDGF, mainly expressed in VSMCs and endothelial cells, promote mitosis and play an important role in the proliferation of VSMCs [6][7][8]37]. The binding of PDGF-BB, a subtype of PDGF released from injured vessels, to its receptor can trigger the activation of downstream and then contribute significantly to VSMCs proliferation [9][10][11][12]. In this paper, PDGF-BB could effectively induce MOVAS proliferation, which was consistent with the previous studies reported.…”
Section: Discussionsupporting
confidence: 87%
“…Compared with DMSO treated group, the expression levels of PCNA and Ki67 were significantly increased in PDGF-BB induced MOVAS cells, but this increment was dampened by OMT treatment ( Figure 2C). (0,5,10,20,40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PDGF stimulates the production of MMP-2 by SMCs and enable the migration of medial SMCs into the intima. 20,36 Moreover, MMP-2 has been associated previously with a more stable plaque phenotype, whereas a high expression of MMP-1, MMP-8, and MMP-9 is associated with more vulnerable plaques. 37,38 MMP3, among other types of proteinases, has been implicated in cleaving pro-HB-EGF to release the mature form of HB-EGF.…”
Section: Discussionmentioning
confidence: 97%
“…For example, overexpression of VEGFa in SNU-5 cells increases MMP-2 expression, whereas downregulation of VEGFa decreases MMP-2 expression (Mao et al, 2014). Also, platelet-derived growth factor-BB increases MMP-2 expression in rat VSMCs, possibly via Rho-associated protein kinase, extracellular signal-regulated kinases, and p38 MAPK phosphorylation (Cui et al, 2014). Also, in a study on carotid plaques, epidermal growth factor (EGF) upregulated MMP-9 activity and increased MMP-1, -9, and EGF receptor (EGFR) mRNA transcripts in VSMCs (Rao et al, 2014).…”
Section: Mmps and Vsm Dysfunction In Vvsmentioning
confidence: 99%